Vitamins D and K as Factors Associated with Osteopathy in Chronic Pancreatitis: A Prospective Multicentre Study (P-BONE Study). Issue 10 (October 2018) - Stigliano, Serena; Waldthaler, Alexander; Martinez-Moneo, Emma; Lionetto, Luana; Robinson, Stuart; Malvik, Marko; Hedstrom, Aleksandra; Kaczka, Aleksandra; Scholdei, Marius; Haas, Stephan; Simmaco, Maurizio; Delle Fave, Gianfranco; et al.
Abstract Background Osteopathy is common in patients with chronic pancreatitis (CP), but previous studies carry several limitations. Vitamin K is essential for bone metabolism, but its role in this setting has never been investigated. Our aim is to assess the prevalence of osteoporosis and osteopenia in CP patients, and to investigate the association between osteopathy and CP features and nutritional parameters, especially vitamin D and K levels. Methods Multicentre cross-sectional study on CP patients diagnosed according to M-ANNHEIM criteria. Bone density was evaluated by dual-energy X-ray absorptiometry and pancreatic function by faecal elastase. Nutritional evaluation included vitamin D and vitamin K. Differences between patients with or without osteopathy were evaluated. The association between investigated variables and bone density were analysed with logistic regression analysis. Results In total, 211 CP patients were enrolled at eight Centres (67% men; mean age 60). In total, 18% had advanced-marked CP, 56% suffered from pancreatic exocrine insufficiency and disease aetiology was alcoholic in 43%. Vitamin D and K were deficient in 56% and 32%, respectively. Osteopenia was diagnosed in 42% and osteoporosis in 22%. In the multivariate analysis, female sex (OR 2.78), age (OR 1.07 per year) and higher BMI (OR 0.84) were associated with the presence of osteoporosis. In male patients, the only factor associated with osteoporosis was vitamin K deficiency (OR 4.23). Conclusion The present data confirm a high rate of osteopathy in CP patients and highlight the relevance of vitamin K deficiency as only factor associated with osteoporosis in male patients for the first time.